PERAN PENDIDIKAN KESEHATAN DALAM MENINGKATKAN PEMAHAMAN DAN SIKAP POSITIF TERHADAP HIV/AIDS PADA IBU YANG TERKENA HIV/AIDS: TINJAUAN LITERATUR - Alnenda Beauty Rofif; Muhammad Sulthan Ilham Ramadhan; Salsabila Rizkamala Putri; Arvia Zeva Eka Putri Armandik; Denny Oktavina Radianto (KOLONI, 2023)
Evaluating the effectiveness of health education programs for mothers living with HIV/AIDS is crucial to ensure that efforts made can provide maximum benefits for the health and well-being of both mothers and children affected by HIV/AIDS. The research method used in this study is literature review. Literature review is a research method that involves searching and analyzing relevant written sources or literature related to the research topic. In this study, the author conducted a search and analysis of literature related to the role of health education in improving understanding and positive attitudes towards HIV/AIDS among mothers living with HIV/AIDS. From the literature review conducted, it was found that health education plays an important role in improving understanding and positive attitudes towards HIV/AIDS among mothers living with HIV/AIDS. Several studies have shown that regular and continuous health education programs can improve knowledge, attitudes, and positive behavior towards HIV/AIDS among mothers living with HIV/AIDS. Health education can be delivered through various media, such as guidebooks, brochures, posters, lectures, group discussions, and digital media. Keywords: Health Education, Understanding and Positive Attitudes, HIV/AIDS, Literature Review.